Sumatriptan Induced Brugada Syndrome, a Rare Presentation of a Commonly Used Drug - Phool Iqbal; Saba Nabavi Monfared; Daniel Hernan Sacoto; Mustafa Bilal Ozbay; Wael Abdelmottaleb; Valentina Turbay Caballero; Muhammad Khalid Tahir; Savi Mushiyev (Clinical Case Reports)
ABSTRACT We aim to highlight an important and rare association of Brugada Syndrome with a commonly used medication, Sumatriptan, which is used as an aborting Migraine headaches. This life‐threatening condition needs early diagnosis and prompt management with vigilant follow‐up for better patient outcomes.